Recreational-Health Use of Saunas by 19-20-Year Old Polish University Students - Podstawski, Robert; Honkanen, Antti; Tuochino, Anja; Kolankowska, Ewelina (Journal of Asian Scientific Research, 2013)
Background: Little research providing reliable information on the popularity of sauna among university students has been found in Polish and foreign literature. Aim: the aim of the research conducted at the University of Warmia&Mazury in Olsztyn was to establish the level of awareness of the benefits of sauna and its popularity among the 1st year students. In addition, the influence of sauna on students’ emotional and physical well-being was also examined. Materials and methods: Total of 1100 students (550 females and 550 males) between 19-20 years old who filled in an anonymous questionnaire took part in the research. Results: Results revealed that although students enjoyed using sauna, more than 60% of women and men had never attended sauna before, and the highest percentage have used sauna only twice or three times in their life. Few women and men visited sauna studios in sports clubs, due to their considerable physical inactivity. First year students have very little awareness of the rules of using sauna, contraindications against its use and recommendations on its practice. It was observed that sauna bathing exerted a highly relaxing and calming influence on the vast majority of students. Conclusions: It was observed that despite a relatively low popularity of sauna among university undergraduates, which was mainly caused by a low awareness of the benefits of sauna on health, the participants confirmed a highly positive influence of sauna bathing on their both physical and emotional well-being. Therefore, sauna treatment may significantly contribute to improving mental health of university students, and for this reason should be promoted and included in the curriculum of physical education.